KARAKTERISTIK FISIKOKIMIA DAN SENSORI KOMBUCHA CASCARA (KULIT KOPI RANUM) - Nurhayati Nurhayati; Sih Yuwanti; Aurora Urbahillah (Jurnal Teknologi dan Industri Pangan, 2020)
Kombucha is usually made from tea leaves (Camellia sinensis L.) extracts added with sugar which is fermented with kombucha starter symbiotic culture of bacteria and yeast (SCOBY) containing. Acetobacter xylinum and yeasts including Saccharomyces cerevisiae. In addition to tea leaves, leather dried coffee (cascara) can be harnessed into beverages like tea steeping. This research aims to ferment cascara tea by SCOBY and characterize the cascara kombucha. These research use two factors i.e. cascara concentrations (1 and 2% b/v) and fermentation periods (4, 8, 12, and 16 days). Sugar was dissolved into water and boilled, added with the cascara while stirring for about 5 minutes, filtered and cooled to 40°C, and then fermented in glass jars with faucets indoor without exposure to direct sunlight for 4, 8, 12, and 16 days. The results showed that concentration of cascara and fermentation time affected the characteristics of cascara kombucha. The effectiveness tests showed that cascara kombucha made from 1% b/v cascara fermented for 8 days resulted in the best and most preferred kombucha. The kombucha characteristics include dissolved solid content of 11.25°Brix, specific gravity of 1.01 g/mL, viscosity of 0.9 cP, brightness (L) 42.0, reddish color (a) 15.1, yellowish color (b) 28.88, pH 3.43, total acid of 0.29, phenolic of 9.9 mg GAE/mL. The kombucha flavor was slightly acidic, murky in color, with slight bitter taste.